Strategy for Extending the Stability of Bio‐oil‐Derived Phenolic Oligomers by Mild Hydrotreatment with Ionic‐Liquid‐Stabilized Nanoparticles. Issue 5 (17th February 2017) - Kim, Kwang Ho; Brown, Robert C.; Daugaard, Tannon; Tivol, William F.; Auer, Manfred; Simmons, Blake; Singh, Seema
Abstract: The development of catalytic transformations and processes is essential to utilize bio‐oil and lignin derivatives. Metal nanoparticles (M‐NPs) stabilized in ionic liquids (ILs) are promising for the catalytic hydrotreatment of bio‐oil because the properties of the catalyst system can be customized by combining the appropriate IL and metal nanoparticles. Herein, we demonstrate an experimental approach to stabilize lignin‐derived phenolics isolated from bio‐oil with ruthenium NPs stabilized by an ionic copolymer in 1‐ethyl‐3‐methylimidazolium acetate ([C2 C1 Im][OAc]). The mild hydrotreatment of phenolic oligomers (POs) was performed with the synthesized M‐NP catalyst at 100 °C for 6 h. Hydrotreatment of the POs resulted in enhanced thermal stability of the POs by as much as a factor of three, as determined by the aging index and by reducing reactive functionalities, which was also confirmed by NMR spectroscopy and GC analysis. The results support our hypothesis that M‐NPs stabilized in ILs can effectively stabilize POs under mild conditions, which could be applicable to any lignin‐derived phenolic. Abstract : Seeking treatment : Ruthenium nanoparticles stabilized in ionic liquid are prepared for the mild hydrotreatment of phenolic oligomers obtained from bio‐oil. The hydrotreated phenolic oligomers show enhanced thermal stability.